ALLERGIC DISEASES AS A RISK FACTOR FOR THE DEVELOPMENT OF BRONCHIOLITHIA - Mukhammadiev Ismail Sulaimanovich; Shavazi Ramiz Nuralievich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Background. Allergic diseases are one of the most common forms of chronic pathology in children and adults. They are characterized by the development of a persistent inflammatory process in the respiratory mucosa, accompanied by increased sensitivity to exogenous and endogenous irritants. Study Objective: To identify the role of allergic diseases as a factor influencing the development, severity, and clinical outcomes of bronchiolitis in children. Study materials and methods. The study involved children aged 1 month to 5 years with a history of acute bronchiolitis. A total of 46 patients were included in the study: Group 1 - 23 children with confirmed allergic diseases (allergic rhinitis, atopic dermatitis, bronchial asthma). Group 2 - 23 children without signs of allergic predisposition.